2017
DOI: 10.1080/19476337.2017.1335347
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol assimilation, acid and bile survival of probiotic bacteria isolated from food and reference strains

Abstract: The evidence shows that probiotics can reduce cardiovascular diseases associated to high cholesterol levels, but it occurs just when they survive gastrointestinal conditions. The aim of this study was to evaluate the ability of reference strains (RS) and food isolates strains (FIS) to survive acid and bile and to determine in-vitro cholesterol assimilation. FIS were more tolerant to acid than RS, showing significantly different growth response. FIS were more resistant to the presence of bile, in order descende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 17 publications
(21 reference statements)
2
16
0
Order By: Relevance
“…The properties of anti-cholesterol of some probiotic lactic acid bacteria have been reported in the literature. Castorena-Alba et al (2018) reported the anti-cholesterol activity of L. fermentum food isolates strains as 57.65% at 4% concentration of oxgall and cholesterol (100 lg/mL). Tulumoglu et al (2014) reported cholesterol assimilation ability of seven L. fermentum strains isolated from Tulum cheese ranging from 12.1 to 45.3%.…”
Section: Cholesterol Assimilationmentioning
confidence: 99%
See 2 more Smart Citations
“…The properties of anti-cholesterol of some probiotic lactic acid bacteria have been reported in the literature. Castorena-Alba et al (2018) reported the anti-cholesterol activity of L. fermentum food isolates strains as 57.65% at 4% concentration of oxgall and cholesterol (100 lg/mL). Tulumoglu et al (2014) reported cholesterol assimilation ability of seven L. fermentum strains isolated from Tulum cheese ranging from 12.1 to 45.3%.…”
Section: Cholesterol Assimilationmentioning
confidence: 99%
“…Consumption of cholesterol rich food can lead to increased blood cholesterol levels and develop hypercholesterolaemia (Castorena-Alba et al, 2018). It has also been reported that hypercholesterolemia is a health problem associated with the dysbiosis of the intestinal microbiota (Lye et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account the published data in the literature, cholesterol assimilation by probiotic strains can range from 0Á86% to more than 40%; however, we usually do not see the same reduction when we use probiotics in the in-vivo conditions, which can be due to the effect of gastrointestinal conditions of the strains, microbial competition, colonization on the epithelial cells, etc. (Belviso et al 2009;Tokatlı et al 2015;Castorena-Alba et al 2018). The outcome of our study indicates that consumption of L. paracasei DTA81 can lead in mice to a statistically significant reduction of total cholesterol and LDL and HDL, which appears very interesting and useful in people who suffer from CVD and CHD.…”
Section: Discussionmentioning
confidence: 65%
“…In their study, Shimizu et al (2015) reported that consumption of probiotics by elderly and hypercholesterolaemic patients could be more effective than in youngsters and individuals with normal lipid levels. Besides, probiotics can reduce cholesterol levels by assimilating and entrapping this molecule into bacterial membranes (Castorena-Alba et al 2018;Bhat and Bajaj 2020). There are numerous species of Lactobacillus and Bifidobacterium that have shown cholesterol assimilation in in-vitro experiments and it has been reported that this ability is strictly strain-…”
Section: Discussionmentioning
confidence: 99%